Wave Characteristics in the Northern Waters of Central Java Based on the Wavewatch III Numerical Model - Efendi, Usman; Ismanto, Aris; Rochaddi, Baskoro; Putra, Sebrian Mirdeklis Beselly (Jurnal Kelautan Tropis, 2024)
The northern coast of Central Java is a strategic development area, but it has the potential for high wave disasters. Planning activities and mitigating maritime disaster risks requires an understanding of wave characteristics. This study analyzes wave characteristics in the northern waters of Central Java using the Wavewatch III numerical model. Significant wave height and wave direction were averaged from 2014 to 2023. The results showed that wave conditions in the northern waters of Central Java tend to be higher in December, January, February, July, August, and September. Meanwhile wave conditions tend to be lower in March, April, May, June, October, and November.